2012
DOI: 10.1128/mcb.06763-11
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Cytoplasmic Turnover of Yeast Ribosomes in Response to Rapamycin Inhibition of TOR

Abstract: The target of rapamycin (TOR) pathway is the central regulator of cell growth in eukaryotes. Inhibition of TOR by rapamycin elicits changes in translation attributed mainly to altered translation initiation and repression of the synthesis of new ribosomes. Using quantitative analysis of rRNA, we found that the number of existing ribosomes present in a Saccharomyces cerevisiae culture during growth in rich medium rapidly decreases by 40 to 60% when the cells are treated with rapamycin. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 74 publications
(98 reference statements)
3
35
0
Order By: Relevance
“…It is well established that yeast entering quiescence lose a substantial percentage of their ribosomes, either through ribophagy or by alternative mechanisms [6,21]. However, while protein synthesis may drop $300-fold upon entry into quiescence [22], not all ribosomes are lost.…”
Section: Stm1p Affects Ribosome Maintenance During Quiescencementioning
confidence: 99%
“…It is well established that yeast entering quiescence lose a substantial percentage of their ribosomes, either through ribophagy or by alternative mechanisms [6,21]. However, while protein synthesis may drop $300-fold upon entry into quiescence [22], not all ribosomes are lost.…”
Section: Stm1p Affects Ribosome Maintenance During Quiescencementioning
confidence: 99%
“…If environmental conditions change, old mRNA will be degraded and will provide source of nucleotides before relatively costly biosynthesis of purines or pyrimidines starts. Also, degradation of rRNA has been described as response during starvation to provide cells with additional energy and nitrogen sources (Pestov & Shcherbik, ; Xu et al, ). Therefore, we hypothesize that if the supply of new purines is halted (stopping de novo synthesis or purine supply from the media), the RNA nucleotide pool could form a source for purines in the cytoplasm.…”
Section: Purine Metabolism In Eukaryotesmentioning
confidence: 99%
“…The authors proposed that ribosomes not engaged in translation, and consequently present as subunits, are sensitive to endoribonuclease cleavage and subsequent degradation (Zundel et al, 2009). Furthermore, TOR inactivation by rapamycin rapidly decreased the cellular ribosome numbers by 40 to 60% in yeast, correlated with rRNA degradation by cytoplasmic nucleases (Pestov and Shcherbik, 2012). These results suggest that TOR controls both new ribosome biosynthesis and degradation of mature ribosomes, in order to adjust the size of the translation machinery to changing environmental conditions.…”
Section: Discussionmentioning
confidence: 72%
“…Recently, it was reported that TOR inhibition by rapamycin triggers a rapid decrease (40-60%) in ribosome content in yeast, through rapid cytoplasmic turnover of the existing ribosomes (Pestov and Shcherbik, 2012). We performed virus-induced gene silencing (VIGS) using the tobacco rattle virus (TRV) system against TOR in MRF1 OE (#1) Arabidopsis plants, to analyze phosphorylation status and ribosome association of Flag:MRF1 in TOR-silenced leaf cells ( Figured 10B and 10C).…”
Section: Phosphorylation and Ribosome Association Of Mrf1 Are Regulatmentioning
confidence: 99%